Interactions between ethanol and cigarette smoke in a mouse lung carcinogenesis model. (12th December 2016) - Balansky, Roumen; Ganchev, Gancho; Iltcheva, Marietta; Nikolov, Manasi; La Maestra, S.; Micale, Rosanna T.; Steele, Vernon E.; De Flora, Silvio
Graphical abstract: Highlights: Cigarette smoke and ethanol are known to synergize in the upper aerodigestive tract. Their interactions in the lower respiratory tract have poorly been explored. Prenatal and postnatal treatments of mice with ethanol caused pulmonary alterations. However, ethanol attenuated smoke-induced preneoplastic and neoplastic lesions in lung. The interaction between smoke and alcohol depends on life stage and target tissue. Abstract: Both ethanol and cigarette smoke are classified as human carcinogens. They can synergize, especially in tissues of the upper aerodigestive tract that are targeted by both agents. The main objective of the present study was to evaluate the individual and combined effects of ethanol and smoke in the respiratory tract, either following transplacental exposure and/or postnatal exposure. We designed two consecutive studies in mouse models by exposing Swiss H mice to oral ethanol and/or inhaled mainstream cigarette smoke for up to 4 months, at various prenatal and postnatal life stages. Clastogenic effects and histopathological alterations were evaluated after 4 and 8 months, respectively. Ethanol was per se devoid of clastogenic effects in mouse peripheral blood erythrocytes. However, especially in mice exposed both transplacentally throughout pregnancy and in the postnatal life, ethanol administration was associated not only with liver damage but also with pro-angiogenetic effects in the lung by stimulating the proliferation of blood vessels. In addition, these mice developed pulmonary emphysema, alveolar epithelial hyperplasias, microadenomas, and benign tumors. On the other hand, ethanol interfered in the lung carcinogenesis process resulting from the concomitant exposure of mice to smoke. In fact, ethanol significantly attenuated some smoke-related preneoplastic and neoplastic lesions in the respiratory tract, such as alveolar epithelial hyperplasia, microadenomas, and even malignant tumors. In addition, ethanol attenuated cigarette smoke clastogenicity. In conclusion, preclinical studies provide evidence that, in spite of its pulmonary toxicity, ethanol may mitigate some noxious effects of cigarette smoke in the respiratory tract.